INITIATING FLIPPED CLASSROOM IN FORMING THE 4C SKILLS AMONG ENGLISH EDUCATION STUDENTS - Kurniawati, Nia (IJLECR (International Journal of Language Education and Cultural Review), 2020)
Flipped classroom enables students to learn new content online by watching video lectures outside the classroom independently with teachers offering more personalized guidance and interaction with students. This study tried to depict an effort of initiating flipped classroom to form the 4Cs among the English Student-Teachers. The aims of this study were to portray the process of initiating flipped classroom, the obstacles, and the students’ 4Cs reflection in the flipped classroom. The study involved four lecturers as collaborators in lesson study of an English Teaching Media subject. The instruments used were observation, interview, and document analysis. In conducting the flipped class, Schoology was utilized. The results showed that, in initiating a flipped class, the lecturers should be really creative in creating the video lectures and other classroom activities as a preclusion to boredom. Besides, the results also denoted emerging capacity of the students’ 4Cs during on line and offline class. Moreover, the lecturers considered flipped classroom as a breakthrough that enables them to have a closer look on the students individually. Nonetheless, the newness of flipped classroom brings about intricacy, since the lecturers should be able to manage online and offline class simultaneously.